Worldwide destinations casebook : the geography of travel and tourism - Boniface, Brian G.; Cooper, Chris (Amsterdam : Elsevier Science, 2005)
Worldwide Destinations: the geography of travel and tourism casebook provides over 40 comprehensive case studies of international tourism destinations. A companion text to the core textbook Worldwide Destinations 4th edition, these cases contextualise the learning and provide real life illustrations of the theories covered. Cases are drawn from all regions of the world and include:* London Docklands: waterfront regeneration and tourism development* Adventure Tourism in Scandinavia* Cultural Tourism in Madrid* Safari Tourism in Zimbabwe* Attractions tourism in New York City* The impact on tourism in Asia* Pro poor tourism initiatives The text provides thorough guidance on using the case studies for maximum benefit to both students and lecturers, with assignments and study tips for each case.
Introduction -- How to use this book -- Cases Illustrating the Elements of the Geography of Travel and Tourism -- Tourism demand and definitions -- Mobilities: concepts of travel, tourism and migration -- Understanding the 'new tourist' -- Analysing the world pattern of international tourism flows -- Tourism destinations -- The Galapagos Islands: balancing resource conservation and tourism development -- The impact of climate change on tourism -- Managing transport at the tourism destination -- European policy and tourism -- Crisis and risk management in tourism -- Tourism destination futures -- Space: the final tourism frontier? -- Tourism as agent of poverty alleviation -- Cases Illustrating Regional Travel and Tourism Geography -- Europe -- London Docklands: waterfront regeneration and tourism development -- The New Forest: managing tourism in an environmentally sensitive area -- The Isle of Man: rejuvenating a cold water destination -- Dublin: tourism in a capital city -- Adventure tourism in Arctic Scandinavia -- Bruges: the impact of tourism in the historic city -- The impact of winter sports tourism in the Austrian and Swiss Alps -- Berlin: the revitalization of a European capital -- The French Riviera: fashion as an influence on resort development -- Payback time for tourism: the Balearic Islands' eco-tax -- Venice: heritage in danger -- A SWOT analysis of tourism in Greece -- Tourism as an agent of economic restructuring in Eastern Europe -- The Middle East and Africa -- Tourism issues in Yemen -- Managing Nile cruise tourism -- CAMPFIRE: local community involvement in safari tourism -- Asia and the Pacific -- Adventure tourism in Nepal -- The Maldives: tourism in an island nation -- Bali: tourism in crisis -- Kangaroo Island: debating tourism development -- The re-visioning of tired destinations: Australia's Gold Coast -- The Americas -- Tourism in New York City -- Nunavut: the involvement of indigenous communities in tourism in the Canadian Arctic -- Tourism in Hawaii -- The regeneration of Rio de Janeiro -- Ecotourism in the Ecuadorian Amazon -- Useful Sources -- Sources to support work on the case studies.
Includes bibliographical references and index.
Keywords: TOURISM